2011
DOI: 10.17221/216/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Changes in species diversity and above-ground biomass of shrubland over long-term natural restoration process in the Taihang Mountain in North China

et al.

Abstract: In order to restore the impaired forest ecosystem in China, great efforts including the banning of the animal grazing and cutting woods for fuel, and implementation of the ‘Grain for Green’ program have been made by the central and local government of China. The objective of this research was to investigate the changes in above-ground biomass and species diversity after 22 years of vegetation recovery efforts in the lower Taihang Mountain of China. The results indicated that over the natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Indeed, Zhou et al [59] found that the reduction of soil erosion in the Loess Plateau was partly attributable to the increase in forest coverage induced by the SLCP. Second, the program is considered to improve the physical properties of the soil structure and reduce nutrient loss to maintain soil fertility, in addition to decreasing river sediments [60]. The effects of the changes in surface runoff and sediment yields have been widely studied [61].…”
Section: Environmental Impactmentioning
confidence: 99%
“…Indeed, Zhou et al [59] found that the reduction of soil erosion in the Loess Plateau was partly attributable to the increase in forest coverage induced by the SLCP. Second, the program is considered to improve the physical properties of the soil structure and reduce nutrient loss to maintain soil fertility, in addition to decreasing river sediments [60]. The effects of the changes in surface runoff and sediment yields have been widely studied [61].…”
Section: Environmental Impactmentioning
confidence: 99%
“…However, the nutrient dynamics in different phases of litter decomposition have not yet been documented for this part of the study area. The variation in vegetation composition has been examined [25], but the role of the change in retaining the soil nutrient content of the aggrading forest ecosystem has not yet been documented. It is imperative to understand changes in the nutrient pattern of different litter types along with the shift in their isotopic properties to know the current situation of an aggrading forest and track its functioning further.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most plant communities in the area are in a secondary stage of disturbance following the near complete eradication of primary, broad-leaved deciduous forests . Most forests have been converted to shrubs or herbaceous vegetation resulting in a deterioration of their ecological environment, with some areas experiencing desertification and a near complete lack of vegetation (Liu et al, 2010(Liu et al, , 2011. In 1999, the Chinese government initiated the Grainfor-Green (GfG) program designed to reduce the deterioration of natural forests and grasslands, increase vegetation coverage on steep slopes, protect water resources, and promote sustainable development in mountainous areas (Zhang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%